(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The corona virus (covid-19) pandemic in Indonesia has forced the Government to make several policies to break the chain of spreading this virus. There are many policies made by the government in several fields, especially the education sector. One of the policies made was distance learning or online learning which was carried out during the Covid-19 pandemic so as not to crowd. This policy changes the habits and behaviour of teachers and students so far. The problem experienced by SMK Pelita Bangsa is the large number of students and teachers it has, SMK Pelita Bangsa must follow the Government’s policy of conducting a distance learning process. Meanwhile, SMK Pelita Bangsa still uses conventional face-to-face learning methods. Based on this description, it is necessary to design a website-based E-Learning which later can help the distance learning process between teachers and students. The results of this E-Learning design research were conducted to provide solutions in the teaching and learning process at SMK Pelita Bangsa. This e-Learning has three main users, namely admin, teachers and students. Some of the learning processes include the teacher uploading materials and assignments, students downloading materials and doing assignments, admin adding teacher and student data and controlling the entire learning process. The programming language for designing E-Learning is the PHP programming language and MySQL as the database.